We're Winning, Don’t Forget - Périot, Jean-Gabriel (Le Yaouanq, Yves ; Dubreuil, Frederic, 2004)
A selection of gradually slowing down video clippings that starts with the scenes of the corporate world, industries, steel works, factories and sweat shops all the way to the scenes of mass demonstrations and protests of the anti-globalists. The final, slow shots of the film portray the violent aftermath of such demonstrations, after the police or the army used force to dismantle them. The soundtrack for this short film was written by Black Emperor and Godspeeed You!.